IMPROVING EFFORTS OF CRITICAL THINKING OF STATISTICS MATERIAL USING PROBLEM BASED LEARNING MODEL IN FIFTH GRADE MELUNG ELEMENTARY SCHOOL - Laelly Wahyuningsih; Wahyudi Wahyudi (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract :The purpose of this study was to describe the application of the Problem Based Learning model to improving student’s critical thinking skills on Mathematics subjects in the fifth grade statistics material at Melung Elementary School. Problem Based Learning is used to stimulate problem-oriented critical thinking. Through the application of Problem Based Learning, students are expected to be able to find solutions to problems discussed in the learning process. The method used is Classroom Action Research (CAR). There were 66.6% of the students in the "fairly critical" category while the other 33.30% were in the "not critical" category. After the actions in cycle I and cycle II, it was found that students who were included in the "very critical" category from the original ones did not increase to 29%, for the "critical" category from the original ones that did not increase to 58% of students. Then it was concluded that the Problem Based Learning model was able to improve students' critical thinking skills in Mathematics subject matter in the fifth grade statistics material at Melung Elementary School. Keywords : Problem Based Learning, critical thinking Abstrak :Tujuan penelitian ini ialah untuk mendeskripsikan penerapan model Problem Based Learning dalam meningkatkan kemampuan berpikir kritis peserta didik pada mata pelajaran Matematika materi statistika kelas V SD Negeri Melung. Problem Based Learning digunakan untuk merangsang berpikir kritis yang berorientasi masalah. Melalui penerapan Problem Based Learning ini, peserta didik diharapkan dapat menemukan pemecahan masalah yang dibahas dalam proses pembelajaran. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK). Ada 66,6% peserta didik dalam kategori “cukup kritis” sedangkan 33,30% lainnya ada dalam kategori “tidak kritis”. Setelah dilakukan tindakan dalam siklus I dan siklus II ditemukan bahwa mahasiswa yang termasuk dalam kategori “sangat kritis” dari yang semula tidak ada meningkat menjadi 29%, untuk kategori “kritis” dari yang semula tidak ada meningkat menjadi 58% peserta didik. Maka disimpulkan bahwa model Problem Based Learning mampu meningkatkan kemampuan berpikir kritis peserta didik dalam mata mata pelajaran Matematika materi statistika kelas V SD Negeri Melung. Kata Kunci : Problem Based Learning, berpikir kritis